ظاهرة المثلية الجنسية: التحريم والتجريم: دراسة وصفية تحليلية مقارنة - الملا، معاذ سليمان راشد محمد; العليمي، راشد سعد (جامعة الكويت - مجلس النشر العلمي, 2023)
الأهداف: يهدف البحث إلى دراسة ظاهرة المثلية الجنسية من خلال بيان مفهومها وتمييزها عن المفاهيم الأخرى، وأيضا بيان أسبابها وآثارها وتقدير خطورتها على واقع المجتمع البشري، كما نهدف إلى بيان حكم الشرائع السماوية والقوانين الجزائية من حيث التحريم والتجريم. المشكلة: يعرض البحث مشكلة الاعتراف بالمثلية الجنسية والمطالبة باعتبارها حقا من حقوق الإنسان بعدما كانت محرمة ومجرمة في سابق الزمان كونها شوهت الفطرة السليمة للإنسان الذي كرمه الله على باقي خلقه. المنهج: اعتمد الباحثان على ثلاثة مناهج علمية الأول هو المنهج الوصفي ببيان ماهية هذه الظاهرة، والثاني هو المنهج التحليلي حيث تناول الباحثان حكم الشريعة الإسلامية في ضوء الكتاب والسنة النبوية الشريفة، كما تناولا موقف المشرع الكويتي من خلال بيان أحكام الدستور والقانون الجزائي، أما المنهج الأخير وهو المنهج المقارن حيث بسط الباحثان ما ورد من أحكام في الشرائع السماوية الأخرى كمقارنة مع الشريعة الإسلامية وموقف القوانين العقابية الأخرى مع القانون الجزائي الكويتي وتم تقسيم موضوعات البحث على هذا الأساس. الخاتمة: خرج البحث بنتائج تكشف عن مدى خطورة هذه الظاهرة على بقاء الجنس البشري والحكمة من تحريمها ومحاربتها منذ القدم عبر الشرائع السماوية، وأظهرت حجم التعارض في المنظمات الدولية ولجانها حول مسألة الاعتراف بها والعمل على ما يتعارض مع هذا الاعتراف، وتناقض بعض الدول في تفسير مفهوم الحرية وتباينها في تجريم هذه الظاهرة وإباحتها. وقد انتهى البحث بتوصيات نرى أنها مهمة في ضوء تلك النتائج. Objectives: The research aims to study the phenomenon of homosexuality by clarifying its concept and distinguishing it from other concepts, as well as explaining its causes and effects and estimating its danger to the reality of human society. We also aim to clarify the rule of divine laws and penal laws in terms of prohibition and criminal- ization. Problem: The research presents the problem of acknowledging homosexuality and claiming it as a human right after it was forbidden and criminal in the past because it distorted the common sense of man whom God honored over the rest of his creation. Methodology: The researchers relied on three scientific approaches, the first is the de- scriptive approach, by explaining the nature of this phenomenon. The second is the an- alytical approach, where the researchers dealt with the rule of Islamic law in the light of the book and the honorable Sunnah of the Prophet. They also dealt with the position of the Kuwaiti legislator by explaining the provisions of the constitution and criminal law. As for the last approach, which is the comparative approach, where the researchers sim- plified the provisions contained in other heavenly laws as a comparison with Islamic law and the position of other punitive laws with the Kuwaiti Criminal law, the research has been divided on this basis. Conclusion: The research came out with results that reveal the extent of the danger of this phenomenon to the survival of the human race and the lesson of the heavenly laws in prohibiting and fighting it since ancient times, and showed the size of the conflict in international organizations and their committees on the issue of recognizing it and working on what contradicts this recognition, and the contradiction of some countries in interpreting the concept of freedom And the contrast in criminalizing and permitting this phenomenon. The research concluded with recommendations that we consider important in the light of these results.
Keywords: الشذوذ الجنسي -- الشريعة الإسلامية -- القانون الجزائي -- الكويت